Pore size evaluation of mesoporous organosilicate films by non-destructive X-ray reflectivity methods. (20th April 2015) - Chien, Yun-San; Yeh, Yu-Shan; Chen, Yen-Song; Leu, Jih-Perng; Fu, Wei-En
Abstract: 200-nm-thick organosilicate films deposited by mixture of tetraethyl orthosilicate (TEOS) and methyltrimethoxysilane (MTMS) dissolving in different cetrimonium bromide (CTAB)/ethanol ratios were characterized in terms of pore size determination and its distribution. Under the toluene ambient, the pores would adsorb the gas hence elevating the whole film density. The X-ray reflectivity (XRR) equipped with mass flow control was utilized to detect the film density increasing. By fitting with Gaussian function and conversing with Kelvin's equation, the pore size was increased from 6.2 to 10.8 Å as the CTAB/ethanol ratio increasing to 0.075. It was attributed to the ethanol and CTAB enhanced the TEOS hollow droplets stability and dissolvability. As the CTAB/ethanol ratio is further increased, the pore size is reversely decreased, owing to the formation of solid microspheres. The non-destructive XRR measurement can evaluate the sub-nano pore sizes and its size distribution, which would fascinate the development and characterization of back-end of line process.